Strengthening National Character Among Senior High School Students Through Islamic Religious Education in Tojo Una-Una Regency - Amin, Sagir Muhammad; Nadirah, Sitti; Idris, Idris (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to analyze the role of Islamic Religious Education (IRE) in strengthening the national character of Senior High School students in Tojo Una-Una Regency. This research employs a qualitative method with a multi-site approach. Data were collected through field observations, in-depth interviews with IRE teachers, school principals, and students, focus group discussions (FGDs), as well as document studies related to school activities. The data sources consist of primary and supporting informants relevant to the context of national character development. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions interactively. The findings reveal that IRE plays a strategic role in shaping students’ national character, which includes attitudes of mutual respect for differences, patriotism, and a sense of responsibility towards the nation. Islamic Religious Education functions not only as a vehicle for knowledge transmission but also as a medium for moral and ethical development aligned with Islamic values. Therefore, IRE serves as a fundamental pillar in safeguarding students from the negative impacts of globalization and in instilling national values in a sustainable manner.